Systematic Review and Meta-analysis of Acupuncture for Modulation of Immune and Inflammatory Markers in Cancer Patients - Wenli Liu MD; Baisong Zhong MD; Richard W. Wagner PhD; M. Kay Garcia DrPH, LAc; Jennifer L. McQuade MD, LAc; Wen Huang MD, PhD; Yisheng Li PhD; Graciela M. Nogueras Gonzalez PhD; Michael R. Spano MS, LAc; Alessandro Cohen MSc; Yimin Geng MS, MSLIS; Lorenzo Cohen PhD (Integrative Cancer Therapies)
Introduction: Inflammation is associated with tumor initiation, and existing tumors are associated with immune suppression locally and systemically. Cancer treatment is also associated with immune suppression. This review evaluates evidence related to the use of acupuncture for modulation of inflammation and the immune system in cancer patients. Methods: Nine databases were searched for prospective, randomized, controlled trials evaluating the use of acupuncture for modulation of the immune system in cancer patients through March 2024. Only studies involving needle insertion into acupuncture points were included. No language limitations were applied. Studies were assessed for risk of bias (ROB) according to Cochrane criteria. The primary outcomes were levels of immune and inflammatory markers. Results: Of 3607 articles identified, 1526 duplicates were omitted, and 2261 articles were screened. Sixty-four (58 Chinese, 6 English) publications met all inclusion criteria and were evaluated for ROB. Forty-seven studies were rated as unclear ROB, and nine studies were rated as high ROB. However, when the blinding and allocation concealment criteria were removed, 12 studies had low ROB. Fifty-six studies were included in the meta-analysis, which found that acupuncture significantly increased interferon gamma (IFN-γ; P  < .01), natural killer (NK) cells ( P  < .01), immunoglobulin G (IgG; P  = .04), immunoglobulin M (IgM; P  = .04), CD3 cells ( P  < .01), CD4 cells ( P  < .01), and the CD4/CD8 cell ratio ( P  < .01), and significantly lowered interleukin (IL)-1 ( P  = .01), IL-4 ( P  < .01), IL-6 ( P  < .01), and C-reactive protein ( P  < .01). Yet except for IFN-γ, there was high heterogeneity of results between studies. No significant differences were found in white blood cells, CD-8, neutrophil levels, IL-2, IL-10, or tumor necrosis factor alpha (TNF-α). Conclusion: The current evidence is insufficient to either support or refute the immunomodulatory effects of acupuncture in cancer patients due to no studies fully meeting the low ROB criterion. The preliminary data, however, are promising. Future studies that are higher powered, with low ROB designs, are warranted.